Law in the World Community - Aikman, Colin C (Victoria University of Wellington Law Review, 1999)
This article is the Inaugural Address given by Professor Aikman, Professor of Jurisprudence and Constitutional Law, Victoria University College, on 11 September 1956. The author discusses the nature of international law in general terms, first by exploring the nature of traditional international law as a set of rules by which states feel themselves bound to observe in their relations with each other. The author then explores the notion that traditional international law was developed as a means for regulating external contacts rather than as the expression of the life of a true society (the favoured approach of Sir Alfred Zimmern). The function of political power is also discussed in the context of the world community, including that of the United Nations. However, the author notes that the United Nations and its related agencies also act on a functional (i.e. social, cultural, economic and humanitarian) field and at a regional level. The author then discusses the role of arbitration, judicial settlement, and the role of moral principles in international affairs. The author concludes that international law requires diversity, commitment, and acceptance.